Resistência e qualidade tecnológica de cultivares de feijão caupi e (Vigna Unguiculata (L.) WALP.) A Callosobruchus maculatus (Fabr.) (Coleoptera : Bruchidae) - Silva, Sabrine Zambiazi da (2011)
From a nutritional point of view, the cowpea is an excellent food choice for its beneficial substances, which makes it ideal for human consumption. However, losses in quality due to the presence of Calossobruchus maculatus, considered the main pest insect of stored beans, which causes hardening of the bean, increases the time required for cooking, changes its flavor and darkens its integument. There is intense search for cultivars able to resist such insect with desirable nutritional and culinary characteristics. This research aimed to evaluate the resistance of eight cultivars to C. maculatus, through free-choice tests, based on biological parameters of insect damages in grains, weight loss, nutritional and technological quality. The BRS Xiquexique cultivar showed resistance, increasing the duration of adult egg cycle, reducing the number of adults emerged and causing weight loss of grains. In addition, the C. maculates showed no preference for feeding from it, while it showed preference for the BRS Caleamé. In general, the infested grains showed higher levels of protein and minerals. It was also observed that the time for cooking parameter had no statistical differences. The results will allow information about the quality of the beans depending on the attack of insects and storage of this legume. There is need for further study of resistance of cultivars in order to contribute to the research of cowpea to the state of Parana, identifying opportunities for investiment.